Cigar and pipe smoking related to four year survival of coronary patients. Issue 5 (May 1983) - Hickey, N; Mulcahy, R; Daly, L; Graham, I; O'Donoghue, S; Kennedy, C
Abstract : Six hundred and thirty-four male patients under 60 years who survived a first attack of unstable angina or myocardial infarction were followed for a period of four years. Details of initial and follow-up smoking habits were examined. Patients who continued to smoke cigarettes or cigars had an excess mortality compared with non-smokers, with those who stopped smoking, and with cigarette smokers who changed to pipe smoking. Pipe smokers who continued smoking the pipe had an observed mortality which was greater than that of the non-smokers, but the numbers were small and the results were not statistically significant. The effect of smoking habit on mortality was not influenced by two other determinants of prognosis: age and severity of initial attack. These results confirm that the long-term prognosis of patients after unstable angina or myocardial infarction may be significantly influenced by smoking habits. They are consistent with the hypothesis that cigar and pipe smoking may have an adverse effect after myocardial infarction but further studies are needed to corroborate the association between cigar and pipe smoking and prognosis of coronary heart disease.